Cynicism as a Physiological Critique in Nietzsche - Horacio de Freitas, Juan (Revista de Filosofía, 2021)
Throughout his intellectual outcome, Nietzsche never ceased to address, although in a largely peripheral manner, the topic of cynicism: first, in its Greco-Roman literary manifestation, mainly represented by Menippean satire, and secondly, as an ethical and epistemological phenomenon. During this second stage, cynicism started to be related to one of Nietzsche’s fundamental notions of his corpus: the physiological critique. To clarify this relationship is the main objective of this article.